Internalisasi Nilai-nilai Kepahlawanan Aria Wangsakara dalam Pembelajaran Sejarah Lokal di SMA Negeri 2 Kota Tangerang: Studi Kasus: SMAN 2 Tangerang - Dwi Riyanti; Rikza Fauzan; Moh. Ali Fadhillah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to determine the local history knowledge of students at SMA Negeri 2 Tangerang City. The method used in this research is a descriptive qualitative method. By describing the results of my research that has been carried out. The main points of discussion in this research include: Aria Wangsakara's heroic values. Internalization of Aria Wangsakara's heroic values raised by students. The advantages and challenges of learning local history based on Aria Wangsakara's heroic values. The instruments used in this research were observation, documentation, interviews with history teachers, interviews with students and distributing questionnairs to students. As for the results of this research, the heroic values of Aria Wangsakara which are told to students make students know the history of the heroic figure Aria Wangsakara. Implementing Aria Wangsakara's heroic values to students which results in them loving their country, being diligent in worship, respecting each other, helping, working together, having a sense of responsibility, and being able to lead. Obstacles and challenges in learning history when conducting research. From the results of this research, it was found that there were still many students who did not know the history of Aria Wangsakara. Students are less orderly in class by chatting, joking and playing with handphones.